Web-Based Programming of Geographic Information System Programming Of Broken Road Mapping In Kampar Regency - Muhammad Rifandi; Beny Setiawan; Novi Yona Sidratul Munti (Journal of Engineering Science and Technology Management, 2021)
In Kampar Regency, congestion occurs at many points, both on protocol roads and village roads. In addition to the fact that Kampar Regency has a large population, the density of transportation or congestion that occurs is also caused by damage to roads. This is also a factor that causes traffic accidents on the highway. The damage to the road could not be handled quickly by the Kampar government. This is because Kampar Regency has a fairly large area, and the survey process that must be carried out is quite time-consuming and costly. Difficulties are also experienced by the community who wants to report a road damage, including because they do not know the procedure that must be done to report it. The Road Reporting System, offers a reporting mechanism, where the reporter can send his report anywhere in Kampar Regency to the Department of Highways of Kampar Regency. The purpose of this research is to make it easier for the public to report damaged road conditions using a damaged road reporting system website that can be accessed online. . The research method used in this research is the waterfall method. This waterfall method has a sequential flow of software starting from planning, analysis, design, implementation, testing, and maintenance. This system design uses Unified Modeling Language (UML) and Object-Oriented Analysis Design (OOAD). The programming language used is PHP Framework Yii and MySQL database.